2010
DOI: 10.1177/0022034510378684
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 and FAK Regulate Periostin Expression in PDL Fibroblasts

Abstract: Recently identified as a key component of the murine periodontal ligament (PDL), periostin has been implicated in the regulation of collagen fibrillogenesis and fibroblast differentiation. We investigated whether periostin protein is expressed in the human PDL in situ and the mechanisms regulating periostin expression in PDL fibroblasts in vitro. With immunohistochemistry, periostin protein was identified in the PDL, with expression lower in teeth with reduced occlusal loading. In vitro application of uniaxial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 22 publications
3
64
0
Order By: Relevance
“…TGF-β increased the expression of periostin, which has been previously shown in gingival and periodontal ligament fibroblasts [8]. However, the effect of TGF-β on periostin expression in tumours has been seldom studied.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…TGF-β increased the expression of periostin, which has been previously shown in gingival and periodontal ligament fibroblasts [8]. However, the effect of TGF-β on periostin expression in tumours has been seldom studied.…”
Section: Discussionmentioning
confidence: 88%
“…It has been shown that periostin can induce EMT via the activation of the PI3K/Akt pathway in prostate cancer cells [6,7]. Additionally, it has been reported that TGF-β can modulate periostin expression in periodontal ligament and gingival fibroblasts [8]. However, similar studies in tumour cells are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Adult periostin null mice were shown to exhibit a periodontal disease phenotype including external root resorption caused by collagen fibril disorganization with defective fibronectin expression (17,22). Additionally, it has been reported that TGF-β can increase periostin expression in PDL (27). In the present study, we evaluated the functional significance of TGF-β signaling on EMT and fragmentation in HERS cells, and suggested that the fragmented HERS cells played as PDL fibroblasts with periostin expression.…”
mentioning
confidence: 78%
“…In situ hybridization and immunohistochemistry showed that periostin is expressed in the PDL, in dental pulp at the sites of hard/soft tissue interfaces in mouse and human tooth [32,33]. Periostin is secreted by fibroblasts and osteoblasts in PDL.…”
Section: Periostin Is Expressed In Bone and Teethmentioning
confidence: 99%
“…TGF-β and BMP are well-known regulators of bone development by stimulating the differentiation of osteoblast progenitors [51,52]. TGF-β, BMP-2, activin, and retinoic acid all stimulate periostin expression in osteoblasts [3,28,33,53,54]. Blocking TGF-β receptor activation or the noncanonical focal adhesion kinase (FAK) pathway reduced periostin mRNA expression.…”
Section: Periostin Expression Is Regulated By Hormones and Growth Facmentioning
confidence: 99%